THE EFFECT OF BURNOUT ON CYBERLOAFING BEHAVIOR WITH JOB STRESS AS A MEDIATING VARIABLE(Study on Employees of the Regional Development Planning Agency of Karangasem Regency) - Ida Ayu Putu Ema Kusumayanti; Made Surya Putra (Adisam Publisher, 2026)
This study aims to analyze the effect of burnout on cyberloafing behavior mediated by job stress in a study of employees of the Regional Development Planning Agency of Karangasem Regency. This study uses a saturated sampling technique that uses the population as the total sample of 52 employees. The method used in this study is a survey method with questionnaire and interview techniques with descriptive statistics and inferential statistical analysis tools of SEM PLS. The results of this study show that burnout has a positive and significant effect on cyberloafing behavior as well as job stress. Job stress has a positive and significant effect on cyberloafing behavior. Job stress also significantly mediates the relationship between burnout and cyberloafing behavior. The theoretical implication of this study is to prove the General Strain Theory and its relation to the research variables